(untitled) (Student Conference Proceedings, 2025)
This paper presents the design and optimization of a prototype of a lightweight drone equipped with Real-Time Kinematic (RTK) technology. The prototype weighs less than 250 grams and is designed for high-precision tasks such as surveying and infrastructure inspections. Key components include a 64 MP camera, a high-speed flight controller (FC), and an electronic speed controller (ESC). Constructing such a drone involves effective weight management and material selection, which enabled the integration of RTK technology, thereby achieving centimeter-level accuracy. This accuracy was validated through thorough flight tests and analyzed using Mission Planner software. This work demonstrates the challenges encountered in the design process, the outcomes of the performance evaluation, and the potential industrial applications of the drone.